Collaborative Governance dalam Pembangunan Desa Inklusif di Desa Bengkala, Kecamatan Kubutambahan, Kabupaten Buleleng - Swastika, I Ketut Agus; Yasintha, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
This research aims to find out how the application of collaborative governance in inclusive development in Bengkala Village, Kubuaddan District, Buleleng Regency. In this research, the writer uses qualitative research with descriptive method. The analysis uses the theory of collaboration success measures from Deseve in Sudarmo (2011) and inclusive development according to Law Number 8 of 2016 concerning Persons with Disabilities in Mufthin (2017). The research findings show that collaboration between the government, the private sector, and the community has been going quite well, but there are several problems such as the dominance of the private sector, the absence of rules governing boundaries between parties, and the lack of information disclosure from the private sector in terms of funding. Then for the findings related to inclusive development, it shows that the inclusive development that has been carried out has been going well. Keyword: Collaborative Governance, Inclusive Development, Disabilities